A5_3 Indiana Jones and the Fridge to Freedom - Mansfield, Tom; Willis, Anthony; Doggett, Ian; Kohli, Sidak s (Physics Special Topics, 2016)
This paper investigates the plausibility of Indiana Jones being able to survive the initial gamma ray radiation from a nuclear explosion by containing himself within a lead-lined fridge. We find that the fridge needs a thickness of lead to be at least 6.83cm for him to be unharmed by the gamma radiation.